Korean territory, Dokdo - Huntai, Jeen; Korea Broadcasting Association (Korea : JRC Inc.)
The connection between the Korean people and Dokdo stretches far back into history. But the Japanese claim that Dokdo is Japanese territory was taken to the tantamount to a declaration of war by Japan against Korea. This film shows the historical and legal basis that Dokdo is Korean territory and inconsistency of Japanese claim
Title from title screen
Music, Kang Myung-Suk
Narration: Kim Do-Hyun
Keywords: Territory, National -- Korea; Territory, National -- Japan; Dokdo (Korea) -- History